Assessment of phytochemicals, antioxidants and in-silico molecular dynamic simulation of plant derived potential inhibitory activity of Thalictrum foliolosum DC. and Cordia dichotoma G. Forst. against jaundice - Raghuvanshi, Disha; Kumar, Sunil; Shukla, Monu Kumar; Kumar, Deepak; Kumar, Dinesh; Verma, Rachna; Nepovimova, Eugenie; Valko, Marian; Alomar, Suliman Y; Alwasel, Saleh H; Kuca, Kamil (Biomedicine & pharmacotherapy, 2022)
Medicinal plants have been exploited for therapeutic purposes since the dawn of civilization and have long been acknowledged essential to human health. The purpose of this research is to examine the scientific evidence for using the therapeutic herbal plants Thalictrum foliolosum DC. and Cordia dichotoma G. Forst. to treat hepatitis illness. The fundamental explanation for the therapeutic relevance of these plants is phytochemicals, which were evaluated qualitatively and quantitatively in three separate extracts with different solvent properties (methanol-polar, chloroform-non-polar, and aqueous-polar as one of the bases of traditional use). Flavonoids, phenols, tannins, saponins, and alkaloids were all evaluated for their presence in plant extracts, and it was observed that methanolic extract had the highest content of phytochemicals among different extracts whereas, the aqueous extract showed least amount of phytochemicals. Additionally, the antioxidant activity of these plants was also evaluated and methanolic extract was revealed with potential antioxidant activity, as also evidenced by the lowest half inhibitory concentration (IC50) values in the DPPH, ABTS, and high %inhibition in µM Fe equivalent of FRAP assays. Following that, the dominant phytochemicals were investigated using ultra-high performance liquid chromatography from the selected plants. Furthermore, default docking algorithms were used to appraise the dominant phytoconstituents for their in-silico investigation, in which rutin was found with the highest binding affinity (8.2 kcal/mol) and interaction with receptor which is further involved in causing jaundice. The receptor is infact an enzyme that is sphingomyelin phosphodiesterase Leptospira interrogans (PDB: 5EBB) which is holded back in its position by rutin and do not interact with Leptospira inferrogans spp which causes jaundice. Overall, the study suggested that these herbs have significant therapeutic properties, and their in-silico analysis strongly recommends further clinical investigations to get insight into the mechanisms of action in curing variety of diseases.
Keywords: flavonoidy; Antitoxicity; Flavonoids; žloutenka; methanol; Plant Extracts; Humans; rutin; Cordia; Rutin; Molecular dynamics; lidé; Antioxidants; rostlinné extrakty; fytonutrienty; Thalictrum; simulace molekulární dynamiky; antioxidancia; Bioactive compounds; Hyperbilirubinemia; Molecular Dynamics Simulation; Methanol; Jaundice; Phytochemicals